KEPUTUSAN INDIVIDU MELAKUKAN MOBILITAS NON-PERMANEN KE KOTA BANDAR LAMPUNG DI PROVINSI LAMPUNG - Budiarty, Ida; Emalia, Zulfa; Hapsari, Cindy Nurul (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2023)
This study explores individual decisions in carrying out natural non-permanent mobility activities to the city of Bandar Lampung. Non-permanent migration increased by 300 percent during 2016-2018. The data used in this research is the 2018 Sakernas micro data for August. Data analysis using the Binary Logistic Regression. The findings show that the variation in the independent variable is able to explain the variation in the dependent variable by 52 percent.. All independent variables (age, wages, education, and distance) are statistically significant in influencing individual decisions to undertake non-permanent migration, except for the variable marital status. The highest odds ratio value for the distance variable, then the education variable. This means that the closer the distance to Bandar Lampung and the better the individual's education, the higher the probability of non-permanent migration to the city of Bandar Lampung. Variable selection is limited due to adjusting the supply of Sakernas micro data files. In the future, it is very important for the government to understand this temporary mobility movement in order to control the short-term and long-term implications of achieving a more equitable distribution of wealth in Lampung Province. Equitable development between urban and rural areas needs to be realized immediately in reducing income inequality and development.